Exploration of Microalgae-Activated Sludge Growth Performance in Lab-Scale Photobioreactors under Outdoor Environmental Conditions for Wastewater Biotreatment - James, Abraham O. [UNESP]; Bankole, Abayomi O. [UNESP]; Pompei, Caroline M. E. [UNESP]; Dantas, Gustavo A. S. A. [UNESP]; Ruas, Graziele [UNESP]; Silva, Gustavo H. R. [UNESP] (MDPI, 2023)
Increasing the volume of untreated and inadequately treated municipal wastewater undermines the circular economy potential of wastewater resources, particularly in low-income regions. This present study focused on and evaluated the performance of native microalgae-activated sludge (MAS) growth for tertiary treatment of anaerobically digested wastewater from an up-flow anaerobic sludge blanket (UASB) in an outdoor lab-scale photobioreactor (2.2 L). Three conditions with distinct MAS inoculum concentrations alongside three controls were operated in batch mode for 5 days hydraulic retention time (HRT) at 11.5:12.5 photo-hours. The MAS inoculum concentration influenced the treatment outcome. The best performance was observed when the MAS concentration was 0.10/0.20 g L−1, and the cell density was 1.60 × 107 cells mL−1, total biomass productivity of 0.10 g TSS L−1 d−1, total phosphorus uptake of 85.1%, and total nitrogen uptake of 66.1%. Logarithmic removal (Log-Re) of bacterial pathogens (water quality indicators) showed Log-Re 3.4 for total coliforms (1.37 × 102 CFU 100 mL−1) and 4.7 for Escherichia coli (0.00 × 100 CFU 100 mL−1). The results revealed optimum remediation performance and nutrient recovery potential with appropriate inoculum concentration, in admiration to advancing the science of circular economy.
Keywords: Escherichia coli removal; microalgae-activated sludge; nutrients recovery; pollutant removal; total coliform